Evolution inequalities with noncoercive w λ 0 -pseudomonotone volterra-type mappings - Kasyanov, P. O.; Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider a class of differential-operator inequalities with noncoercive w λ 0 -pseudomonotone operators. The problem of the existence of solutions of the Cauchy problem for these inequalities is investigated by using the Dubinsky method. A priori estimates for these solutions and their derivatives are obtained. We give a model example that illustrates the results and generalizations obtained.